A parametric investigation on the seismic capacity of masonry cross vaults. (1st October 2017) - Gaetani, Angelo; Lourenço, Paulo B.; Monti, Giorgio; Milani, Gabriele
Highlights: A non-commercial limit analysis software was adopted. The parametric study allowed identifying a few meaningful failure mechanisms. The results were processed through linear multiple regression analyses. Tensile strength, thickness and rise are the most influencing parameters. A simplified procedure to evaluate the seismic capacity is presented. Abstract: Considering the relevance and the artistic value of cross vaults in European seismic prone areas, a parametric study on the seismic capacity of this element is presented. In particular, the behaviour of the so-called groin vault is discussed, i.e. intersection at a right angle of two semi-circular barrel vaults. The influence of span, rise, thickness, infill, and masonry tensile strength is investigated with respect to two boundary conditions, representative of typical vault configurations within heritage buildings. The analyses were performed using an upper bound approach of standard limit analysis. For the sake of clarity, the adopted code framework is briefly reviewed. With the aim of identifying the most frequent failure mechanisms, the outcomes of the parametric analysis have been visually inspected and sorted according to the input parameters. Aiming toward a simplified assessment criterion, the resulting list of parameters was subsequently processed through multiple linear regression analyses that can help practitioners in quick seismic evaluation.